Chemoattraction and Recruitment of Activated Immune Cells, Central Autonomic Control, and Blood Pressure Regulation - Elsaafien, Khalid; Korim, Willian S.; Setiadi, Anthony; May, Clive N.; Yao, Song T. (Frontiers in Physiology, 2019)
Inflammatory mediators play a critical role in the regulation of sympathetic outflow to cardiovascular organs in hypertension. Emerging evidence highlights the involvement of immune cells in the regulation of blood pressure. However, it is still unclear how these immune cells are activated and recruited to key autonomic brain regions to regulate sympathetic outflow to cardiovascular organs. Chemokines such as C-C motif chemokine ligand 2 (CCL2), and pro-inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) and interleukin 1 beta (IL-1β), are upregulated both peripherally and centrally in hypertension. More specifically, they are upregulated in key autonomic brain regions that control sympathetic activity and blood pressure such as the paraventricular nucleus of the hypothalamus and the rostral ventrolateral medulla. Furthermore, this upregulation of inflammatory mediators is associated with the infiltration of immune cells to these brain areas. Thus, expression of pro-inflammatory chemokines and cytokines is a potential mechanism promoting invasion of immune cells into key autonomic brain regions. In pathophysiological conditions, this can result in abnormal activation of brain circuits that control sympathetic nerve activity to cardiovascular organs and ultimately in increases in blood pressure. In this review, we discuss emerging evidence that helps explain how immune cells are chemoattracted to autonomic nuclei and contribute to changes in sympathetic outflow and blood pressure.